Associations Between Posttraumatic Stress Disorder, Emotion Dysregulation, and Alcohol Dependence Symptoms Among Inner City Females. Issue 3 (28th July 2016) - Goldstein, Brittany; Bradley, Bekh; Ressler, Kerry J.; Powers, Abigail
Abstract : Objective: The purpose of this study was to examine how emotion dysregulation (ED) might help explain the relationship between posttraumatic stress disorder (PTSD) and alcohol dependence (AD) symptoms in females. Method: Participants included 260 women from primary, diabetes, and gynecological clinics of an urban public hospital. This is a primarily African American sample (96.9%), including individuals reporting exposure to at least 1 traumatic event. We examined the associations and predictability patterns between severity of PTSD symptoms, ED, and AD symptoms. Results: Using linear regression analyses, PTSD avoidance and numbing symptoms and ED were significant predictors of AD symptoms. When looking at specific dimensions of ED, one's inability to engage in goal‐directed behavior under strong emotional influences showed a full indirect effect on the relationship between PTSD avoidance and numbing symptoms and AD symptoms. Conclusion: Our findings suggest that having poor emotion regulation skills may help explain why females with PTSD become dependent on alcohol.